MODERN APPROACHES IN CREATING INTERIORS OF OFFICE PREMISES - Іщук, Олексій; Булгакова, Тетяна (SWorldJournal, 2024)
In the article discusses the main modern approaches to creating interiors of office premises based on the analysis of projects of Ukrainian and foreign designers. The research is based on the method of complex analysis and synthesis of objective data fro